Heterologous Coproduction of Enterocin A and Pediocin PA-1 by Lactococcus lactis: Detection by Specific Peptide-Directed Antibodies - Martínez, José M. (American Society for Microbiology, 2000)
Antibodies against enterocin A were obtained by immunization of rabbits with synthetic peptides PH4 and PH5 designed, respectively, on the N- and C-terminal amino acid sequences of enterocin A and conjugated to the carrier protein KLH. Anti-PH4-KLH antibodies not only recognized enterocin A but also pediocin PA-1, enterocin P, and sakacin A, three bacteriocins which share the N-terminal class IIa consensus motif (YGNGVXC) that is contained in the sequence of the peptide PH4. In contrast, anti-PH5-KLH antibodies only reacted with enterocin A because the amino acid sequences of the C-terminal parts of class IIa bacteriocins are highly variable. Enterocin A and/or pediocin PA-1 structural and immunity genes were introduced in Lactococcus lactis IL1403 to achieve (co)production of the bacteriocins. The level of production of the two bacteriocins was significantly lower than that obtained by the wild-type producers, a fact that suggests a low efficiency of transport and/or maturation of these bacteriocins by the chromosomally encoded bacteriocin translocation machinery of IL1403. Despite the low production levels, both bacteriocins could be specifically detected and quantified with the anti-PH5-KLH (anti-enterocin A) antibodies isolated in this study and the anti-PH2-KLH (anti-pediocin PA-1) antibodies previously generated (J. M. Martínez, M. I. Martínez, A. M. Suárez, C. Herranz, P. Casaus, L. M. Cintas, J. M. Rodríguez, and P. E. Hernández, Appl. Environ. Microbiol. 64:4536–4545, 1998). In this work, the availability of antibodies for the specific detection and quantification of enterocin A and pediocin PA-1 was crucial to demonstrate coproduction of both bacteriocins by L. lactis IL1403(pJM04), because indicator strains that are selectively inhibited by each bacteriocin are not available.